Ambulatory Surgical Services Provided Under California Workers' Compensation An Assessment of the Feasibility and Advisability of Expanding Coverage - Wynn, Barbara O. (RAND Corporation, 2014)
Report examines whether common workers' compensation inpatient procedures with short lengths of stay should be added to California's Official Medical Fee Schedule for ambulatory surgical centers. Authors analyze ASC health and safety requirements, assess how Medicare criteria for whether procedures can be safely performed on an outpatient basis apply to workers' compensation patients, and consider alternatives for setting fee schedule allowances.